Myeloid-Derived Suppressor Cells and Clinical Outcomes in Children With COVID-19 - Bline, Katherine; Andrews, Angel; Moore-Clingenpeel, Melissa; Mertz, Sara; Ye, Fang; Best, Victoria; Sayegh, Rouba; Tomatis-Souverbielle, Cristina; Quintero, Ana M.; Maynard, Zachary; Glowinski, Rebecca; Mejias, Asuncion; et al. (Frontiers in Pediatrics, 2022)
Background: Although children with COVID-19 account for fewer hospitalizations than adults, many develop severe disease requiring intensive care treatment. Critical illness due to COVID-19 has been associated with lymphopenia and functional immune suppression. Myeloid-derived suppressor cells (MDSCs) potently suppress T cells and are significantly increased in adults with severe COVID-19. The role of MDSCs in the immune response of children with COVID-19 is unknown. Aims: We hypothesized that children with severe COVID-19 will have expansion of MDSC populations compared to those with milder disease, and that higher proportions of MDSCs will correlate with clinical outcomes. Methods: We conducted a prospective, observational study on a convenience sample of children hospitalized with PCR-confirmed COVID-19 and pre-pandemic, uninfected healthy controls (HC). Blood samples were obtained within 48 hours of admission and analyzed for MDSCs, T cells, and natural killer (NK) cells by flow cytometry. Demographic information and clinical outcomes were obtained from the electronic medical record and a dedicated survey built for this study. Results: Fifty children admitted to the hospital were enrolled; 28 diagnosed with symptomatic COVID-19 (10 requiring ICU admission) and 22 detected by universal screening (6 requiring ICU admission). We found that children with severe COVID-19 had a significantly higher percentage of MDSCs than those admitted to the ward and uninfected healthy controls. Increased percentages of MDSCs in peripheral blood mononuclear cells (PBMC) were associated with CD4+ T cell lymphopenia. MDSC expansion was associated with longer hospitalizations and need for respiratory support in children admitted with acute COVID-19. Conclusion: These findings suggest that MDSCs are part of the dysregulated immune responses observed in children with severe COVID-19 and may play a role in disease pathogenesis. Future mechanistic studies are required to further understand the function of MDSCs in the setting of SARS-CoV-2 infection in children.